2022
DOI: 10.3390/met12020254
|View full text |Cite
|
Sign up to set email alerts
|

Si-Al-N-O Multi-Layer Coatings with Increased Corrosion Resistance Deposited on Stainless Steel by Magnetron Sputtering

Abstract: This work studies single-layer (Al-Si-N) and multi-layer (Al-Si-N-O/Al-Si-O) coatings deposited by magnetron sputtering on stainless steel specimens (AISI 321), which can be used under aggressive conditions. The multi-layer coating consists of six alternating layers of Al-Si-N-O and Al-Si-O with a thickness of 0.9 µm and 0.2 µm, respectively. The structural-phase state and the chemical composition of the coatings were studied by transmission and scanning electron microscopy and XPS analysis. It was revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Thus, multilayer cermet coatings (Metal/nitride ceramics/ Metal/oxide ceramics) acquired the properties of each of the layers, and a synergistic effect appeared. In addition, the layering created several barriers to the diffusion of chloride ions from the environment [13,16]. The thinness of these layers increased the elasticity of the final coated material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, multilayer cermet coatings (Metal/nitride ceramics/ Metal/oxide ceramics) acquired the properties of each of the layers, and a synergistic effect appeared. In addition, the layering created several barriers to the diffusion of chloride ions from the environment [13,16]. The thinness of these layers increased the elasticity of the final coated material.…”
Section: Discussionmentioning
confidence: 99%
“…The coating may have a different composition, and the methods of formation may be different [1][2][3][4][5][6][7][8][9][10]. Magnetron sputtering makes it possible to form layers of various thicknesses, compositions, and characteristics, including metal and ceramics layers on various substrates [11][12][13]. By changing the composition of the target and the composition of the gas atmosphere in the vacuum chamber, multicomponent layered coatings can be sprayed, modeled, and combined for the tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The necessary properties of all types of coatings are high adhesion, continuity, and resistance to aggressive media. A protective layer can be formed on the surface by various methods: electrochemical [3,4] and chemical ones [5,6], thermal diffusion [7,8], laser cladding [9,10], magnetron sputtering [11][12][13][14][15], plasma deposition [16], ion implantation [17][18][19][20][21], etc.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a significant part in forming a barrier between metal surfaces and corrosive media, in addition to improving wear and hardness by modifying the surface's characteristics and forming a new transition region between the deposited layer and the base metal. Metal protection can be achieved by forming thin layers on their surface with thicknesses ranging from a few microns to many atomic layers [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been done in this field; Ibrahim et al [17] found that the corrosion resistance of stainless steel 316L was improved after coating it with epoxy-zinc oxide nanocomposite. Also, Dorofeeva et al [8] reported that stainless steel coated with multi-layers exhibits significantly (tenfold) greater corrosion resistance than the substrate. The coating is made using either the chemical vapour deposition (CVD) or physical vapour deposition (PVD) processes, and sometimes both together, to increase their lifespan.…”
Section: Introductionmentioning
confidence: 99%